Citric acid tumble soaking as an antimicrobial treatment for ox tripe - Rosario, Jinky Rose Solomon
ABSTRACT This study investigated the efficacy of citric acid tumble soaking (CATS) as an antimicrobial treatment for ox tripe. The treatments of ox tripe were done using 2.5%, 5.0% and 7.5% citric acid aconcentratio tumble soaked for 5, 10, or 15 min. Microbial and physicochemical characteristics were monitored during a 42-d frozen storage, while sensory characteristics were evaluated on freshly CATS treated ox tripe. Significant decrease in pH, texture, TPC, TCC and E.coli counts were observed upon CATS treatment and during storage period. The citric acid tumble soaked ox tripe were given a sensory acceptance ratings of up to 'like very much'. Citric acid treatment affected 3.00-4.00 log reduction in TPC and 99.5-99.7% reduction in TCC and E.coli counts. Salmonella spp. was not completely eliminated by CATS treatment throughout storage period. Survival study was done to establish the antimicrobial activity of CATS treatment on Salmonella typhimurium. The CATS treatment of ox tripe reduced the total bacterial population on NA by 34.68-47.37% and up to 83.30% on BSA, with the reduction relatively increasing with increasing concentration of citric acid.